Learning Intensity and Visual Learning Style on Learning Outcomes - Muslim, Fachruddiansyah; Ekawarna, Ekawarna; Ramalia, Aminah; Wirayuda, Ricky Purnama; Chen, Diki (Journal of Education Reseach and Evaluation, 2022)
Learning activities do not have to be done for a long time. Good learning intensity is carried out regularly will make learning activities a habit. The learning process also needs to be supported by a learning style that suits the characteristics of students. This study aimed to analyze the intensity of learning-on-learning outcomes, visual learning styles on learning outcomes, and learning intensity and visual learning styles on learning outcomes. This type of research is quantitative with a descriptive quantitative approach. The sample used was 65 students with purposive sampling. Data collection method using questionnaire and documentation. The instrument used is a questionnaire. Data analysis techniques are qualitative descriptive analysis, quantitative, and inferential statistics. The results showed a significant effect of learning intensity on learning outcomes in macroeconomic theory courses. There is a significant effect of visual learning style on learning outcomes in macroeconomic theory courses. There is a significant influence between visual learning styles on learning outcomes of macroeconomic theory courses. There are significant effects of visual learning style on learning outcomes of macroeconomic theory courses. It is concluded that there is a simultaneous influence between learning intensity and visual learning style on learning outcomes in macroeconomic theory courses.